Analysis of BTA16 CNC Machine Performance Improvement with Total Productive Maintenance Approach - Erik Odi Wijaya; Welly Atikno; Indra Setiawan; Rendy Susanto; Hibarkah Kurnia (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2022)
Machinery or production equipment was the most important part of a production system. Machines need effective and efficient maintenance to be able to guarantee and support the production process to operate properly. The gas filter industry is an industry that produces air and gas filters. The gas filter industry has many production machines, one of which is CNC BTA16. This machine often has problems such as downtime that interfere with smooth production. The purpose of this study was to determine the problems in the CNC BTA16 production machine and provide recommendations for improvements to improve machine performance. The approach used is Total Productive Maintenance. Problem analysis was carried out through Focus Group Discussions with experts. The results showed that the cause of the engine is not optimal comes from abnormal heat in the gearbox on the engine spindle component caused by operator error when inputting data. The results of the calculation of the OEE value on the BTA16 CNC machine during the January – December 2021 period, the average OEE value was 73%. Suggested improvements are to make a special schedule for maintenance, check all speeches, and conduct training for employees to improve knowledge and skills.